Oculomotor disorders in Huntington's chorea. Issue 7 (July 1979) - Avanzini, G; Girotti, F; Caraceni, T; Spreafico, R
Abstract : Electro-oculographic recordings were obtained from 11 patients with Huntington's disease. Significant reduction of saccadic velocity was constantly found. In all the patients vertical saccades were much more impaired than horizontal. When present, vertical saccades showed long latency, low amplitude, low velocity, and disturbances related to blinking. Following movements were jerky, and ability to perform repeated rhythmic movements was impaired. These results are in agreement with previous observations and underline the selective defect of rapid movements as a characteristic feature of Huntington's disease. Further, they suggest a possible correlation between the difficulty in performing repeated ocular movements and the impaired execution of gestural sequences involving a succession of different fundamental movements.